Material Lokal di Bali Utara - I Putu Teja Artawan; Hima Santhani; Putu Pritayuni Paramisiwi; I Wayan Runa; Ni Komang Indra Mahayani (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2021)
As a Regency with the largest area on the island of Bali, Buleleng Regency has a wealth of natural materials that are used as building materials by the community, has a wet and dry tropical climate as well as a topographical diversity ranging from highlands, lowlands, to coastal areas, making the region unique. diversity of vegetation and rock layers. The geographical conditions in Buleleng Regency are represented in the buildings in the area, both in community buildings and tourism accommodation buildings. In the eastern part of Buleleng Regency, namely in Tejakula District, there were 14 types of materials that were successfully observed. The materials available are very diverse, ranging from foundation materials, pile structures, to roofs. There are various ways of processing materials used as building materials, ranging from traditional methods to those that have received a touch of technology. Utilization of natural materials around the Tejakula area is important in an effort to maintain a more friendly environment for nature, where local materials have properties that are more adaptable to the natural surroundings, as well as the embodiment of sustainable architecture that exists there, so as to create environmental harmony.